Experimental and numerical study on water-lubricated rubber bearings. Issue 2 (4th March 2014) - Wang, You-Qiang; Shi, Xiu-Jiang; Zhang, Li-Jing
Abstract : Purpose: – Water-lubricated rubber bearing is one of the most appropriate bearings for underwater use. The most popular design used widely today is the straight fluted rubber bearing. The special configuration leads to partial hydrodynamic lubrication and low load capacity. A new bearing bush structure with two cavities which is favorable for constructing continuous hydrodynamic lubrication was designed and studied. The paper aims to discuss these issues. Design/methodology/approach: – A new bearing bush structure with two cavities which is favorable for constructing continuous hydrodynamic lubrication was designed. The apparatus for studying the tribological behaviors of the two types of water-lubricated rubber bearings has been devised and established in the paper. The experimental studies on the tribological properties of the rubber bearings have been conducted under different loads and velocities. The eccentricity ratio of the new structure rubber bearing with two cavities was measured in experiment and the load capacity was calculated by numerical simulation. Findings: – The experimental results show that the friction coefficient decreases with increasing velocity; the friction coefficient increases sharply with the rising temperature, the friction coefficient increases at first and then decreases with increasing load for fluted rubber bearings. The numerical results were in good agreement with the experimental results. The numerical results show that complete hydrodynamic lubrication can be formed in the new designed rubber bearing with two cavities. The experimental and numerical results all indicate that there is an appropriate bearing clearance which the friction coefficient is minimum and the load capacity is maximum. Originality/value: – A new bearing bush structure with two cavities which is beneficial to constructing continuous hydrodynamic lubrication film was designed. A new apparatus for studying the tribological behaviors of the two types of water-lubricated rubber bearings has been devised and established. Experimental and numerical study on the new structure rubber bearing were conducted in the paper.